NGF and PI3K/Akt signaling participate in the ventral motor neuronal protection of curcumin in sciatic nerve injury rat models - Sang, Qiuling; Sun, Daju; Chen, Zonghan; Zhao, Weijia (Biomedicine & pharmacotherapy, 2018)
It has been reported that sciatic nerve injury (SNI) leads to degeneration, damage, and apoptosis of motor neurons. Nerve growth factor (NGF) plays a pivotal role in regeneration and reestablishment of neuronal function via activating PI3K/Akt survival signaling pathways. Curcumin owns neuroprotective effect following brain injury. In the present study, we attempt to investigate underlying mechanism of neuroprotective effect of curcumin through elucidating its correlation with NGF and PI3K/Akt signaling pathways in vitro and in vivo. PC-12 cells were exposed H2O2 in order to induce neuron cell injury and cells were then treated with curcumin. Caspase-3, NGF level and Akt phosphorylation were determined using flow cytometry and western blotting. Then, cells were treated with NGF specific siRNA followed by measurement of apoptosis, NGF and Akt phosphorylation levels. In animal model, rats were subjected to SNI and then randomly designated into four different groups: curcumin, curcumin + LY294002, curcumin + NGF shRNA, and negative controls and 12 rats in each group (n = 12). After four weeks of continuous treatment, tissue samples were obtained and subjected to TUNEL, NeuN double staining and western blotting. Curcumin significantly reduced the number of apoptotic cells induced by H2O2 and this effect was associated with upregulation of TrkA, Akt and downregulation of p17. ProNGF level was significantly decreased while mature NGF level was increased with curcumin treatment. When NGF was suppressed, anti-apoptotic effect of curcumin was attenuated. In addition, inhibition of PI3K/Akt results in increased apoptotic rate compared to vehicles following curcumin treatment which was reflected by decreased p17, Ki67, and cyclin D1. Suppression of NGF and inhibition of PI3K led to increased neuron cell death through increasing proNGF and decreasing mNGF, Akt, TrkA, p75NTR, and p17. Our findings revealed that curcumin exerts its protective effect against injured neurons through stimulating NGF release which further activates TrkA and PI3K/Akt cell survival signaling.